(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
This paper is basically concerned with finding the solution using formulae, existence and uniqueness of solutions of impulsive fractional differential equations with ABC (Atangana-Baleanu-Caputo) fractional derivative with non-singular Mittag-Leffler kernel. Our examination depends on non-singular fractional analysis and few techniques of fixed-point theory. An example is illustrated to clarify the proved concepts.